Measurement of Subcarinal Angle: A Cadaveric study - Shrestha, Anusuya; Ranjit, Nirju; Bhandari, Rosha; Adhikari, Bidur; Gautam, Jyoti (Journal of Institute of Medicine Nepal, 2019)
Introduction: The bifurcation of trachea into two primary bronchi at the level of fourth thoracic vertebra creates an angle at the bifurcation. This angle can be seen clearly in routine chest X-rays where the measurement can throw light on many medical conditions within the mediastinum. This study aimed at finding the subcarinal angle, which is the angle formed by inferior borders of two primary bronchi. Methods: The measurements were taken from photographs of tracheal specimen of 92 cadavers, 63 male and 29 female. Angle was measured by photographic software and analysis of subcarinal angle was done in the study population. Results: The mean subcarinal angle was found to be 41.09° with standard deviation of 17.14°. This measurement was found to be significantly more in males (68.02± 15.72°) than in females (60.14 ± 17.71°). Conclusion: The subcarinal angles in the study population were seen to be different among sexes. Also, the mean subcarinal angles from other studies, radiological or on specimen were close to the observations made in this study.